Hygiene and restraint of pigs is associated with absence of Taenia solium cysticercosis in a rural community of Mexico La higiene y el confinamiento de cerdos están asociados con la ausencia de cisticercosis por Taenia solium en una comunidad rural de México - Sonia Vázquez-Flores; Gilberto Ballesteros-Rodea; Ana Flisser; Peter M. Schantz (Instituto Nacional de Salud Pública, 2001)
Objective. To determine the prevalence and risk factors associated to pig cysticercosis in a rural community of Veracruz, Mexico. Material and Methods. Swine cysticercosis was diagnosed by tongue palpation and circulating antibodies in pigs kept in 178 household backyards. Risk factors were assessed by interviewing owners to collect information on pig breeding conditions and demographic characteristics. Results. None of the 53 pigs studied showed cysts in the tongue, nor antibodies against Taenia solium in Western blot assays. Latrines were available in 91% of the houses and pigs were kept in restrained areas. Conclusions. The present study shows that pig breeding under restraint with basic hygiene and sanitary conditions, may be effective and practical interventions to restrain Taenia solium in rural communities. The English version of this paper is available too at: http://www.insp.mx/salud/index.html Objetivo. Determinar la prevalencia y factores de riesgo asociados con cisticercosis porcina en una población rural de Veracruz, México. Material y métodos. Se diagnosticó cisticercosis porcina por medio de palpación lingual y anticuerpos circulantes en cerdos de traspatio en 178 casas. Se analizaron los factores de riesgo mediante una encuesta a los dueños respecto a las condiciones de crianza de los cerdos y sus características demográficas. Resultados. Los 53 cerdos estudiados fueron negativos al metacéstodo de Taenia solium por palpación lingual y para la presencia de anticuerpos contra este agente por inmunoelectrotransferencia. El 91% de las casas contaban con letrinas y los cerdos estaban confinados en zonas restringidas. Conclusiones. Este estudio muestra que el confinamiento de cerdos puede explicar la ausencia de Taenia solium en comunidades rurales, y sugiere que es factible y práctico establecer medidas de intervención. El texto completo en inglés de este artículo también está disponible en: http://www.insp.mx/salud/index.html